2007
DOI: 10.1080/10641950701548240
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen Concentration and Factor VIII Activity in Women with Preeclampsia

Abstract: This study has shown a novel increase in both fibrinogen concentration and factor VIII activity in pregnant women with preeclampsia compared with values obtained from women with normal or non-preeclampsia complicated pregnancies, with women with preeclampsia twice as likely to have a raised fibrinogen concentration and increased factor VIII activity. These changes may contribute to the hypercoagulability seen in preeclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 20 publications
2
11
0
Order By: Relevance
“…We have also shown that the distribution of HRG in placental tissue is altered in early-but not in late-onset preeclampsia. This study supports earlier findings that pregnancy alters the balance of the coagulation system and that this imbalance is even more pronounced when the pregnancy is complicated by preeclampsia (8,9).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We have also shown that the distribution of HRG in placental tissue is altered in early-but not in late-onset preeclampsia. This study supports earlier findings that pregnancy alters the balance of the coagulation system and that this imbalance is even more pronounced when the pregnancy is complicated by preeclampsia (8,9).…”
Section: Discussionsupporting
confidence: 92%
“…These thrombi are especially prevalent in the preeclamptic placenta. It has been shown that early‐onset preeclampsia is associated with a hypercoagulable state (8) and a disturbed fibrinolytic system. Additionally, women with severe early‐onset preeclampsia display increased D‐dimer levels as compared to women with normal pregnancy (9).…”
Section: Discussionmentioning
confidence: 99%
“…We did not detect any difference in fibrinogen in women who later developed CH, though preeclampsia is known to be a hypercoagulable state, primarily due to increases in thrombin and markers of thrombin activity, [9, 19, 20]. Fibrinogen has been reported to be higher in women with PE, and has been shown to correlate with severity of disease [21, 22]. Our evaluation of fibrinogen was before the onset of clinical disease in women who developed term PE, rather than more severe, early onset, forms of preeclampsia.…”
Section: Discussionmentioning
confidence: 95%
“…All of the above-mentioned pathways are reported to contribute to the pathogenesis of preeclampsia (45). Circulating levels of total fibrinogen increase 2-fold during the course of a healthy pregnancy (46) and are significantly increased in preeclampsia (7,47), providing a link with the hypercoagulable states of pregnancy and with preeclampsia in particular. Moreover, increased fibrinogen levels have been linked to an increased risk of coronary artery disease (48).…”
Section: Discussionmentioning
confidence: 99%